The Activities and Physical Factors of Public Space in Nakhon Si Thammarat Old Town - Sukkan, Monchadapon; Kimnuan, Pornthip (Asian Creative Architecture, Art and Design, 2021)
This research aims at studying the use patterns and physical factors of the public spaces in Nakhon Si Thammarat Old Town, by studying the theories, meaning of public spaces, 3 types of activities in public spaces and 8 the physical factors affect to success in public space use. The research methods contain a site survey on a sampling of 19 public spaces that are categorized into 5 types which the criteria used for selecting the study area were the major type of activities: a historical space, a government space, a recreation space, a historic mixed recreation space, a historic mixes government and recreation space. The sample group consisted of 400 people who responded to the questionnaire surveying use pattern and 8 physical factors that influencing the public space utilization. Then compare the results relationship between use pattern and physical factors of each type of public space. The results reveal 1) The Popularity of usage patterns same activities in 5 types is alternative activities, the necessary activities found in 4 types of public space and in social activities found in 1 type of public space respectively. 2) The important physical factors that influencing the public space utilization of public space 5 types are accessibility which contribute to activities in public spaces. 3) The physical factor influencing the use of each type of public space: the physical identity factor which is important to 3 types of public spaces. The location is nearly the community zones which is important to 2 types of public spaces. Landscape and shady, Safety and variety of activities, Flexible activities and Landscape elements was found that each factor was important to only one type of public space.